Animated Movie Clips as Teaching Media for EFL Students in Listening Skill - Gede Weda Rukmana; Ni Nyoman Padmadewi; I Gusti Ayu Agung Manik Wulandari (Universitas Pendidikan Ganesha, 2025)
Listening skills are one of the most challenging aspects in learning English as a Foreign Language (EFL) because they require students to comprehend spoken input, capture meaning, and process it in real time. However, limited exposure, monotonous learning resources, and less engaging media often become obstacles for students. This study aims to analyze the significant effect of using animated movie clips as a learning medium on the listening skills of EFL students. This research employed a quasi-experimental design with a post-test only control group design. The population of this study consisted of eleventh-grade students, and purposive sampling was used to select the research participants. Data analysis was conducted using descriptive and inferential statistics. The results indicate that the mean score of the experimental group (82.05) was higher than that of the control group (76.82). The hypothesis testing using a t-test revealed a significant difference after the use of animated movie clips as a learning medium in students’ listening skills. In addition, the questionnaire administered to the experimental group showed that most students responded positively to the use of animated movie clips, as they were perceived to be engaging, motivating, and helpful in understanding listening materials. Therefore, it can be concluded that the use of animated movie clips has a significant effect on the listening skills of EFL students. The implications of this study suggest that teachers should integrate dynamic and authentic audio-visual media into the learning process to enhance listening comprehension and create a more interactive learning environment.